Multi-component platinum-bismuth-based intermetallic ordered nanosheet as well as preparation method and application thereof
By using multi-component platinum bismuth-based intermetallic ordered nanosheets as catalysts, the problem of insufficient activity and stability of traditional catalysts is solved, and efficient electrocatalytic performance is achieved, especially stability under acidic conditions.
Patent Information
- Application Number
- CN202411617952.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-13
AI Technical Summary
Traditional platinum-based polymetal alloy catalysts have insufficient catalytic activity and stability in fuel cells, making it difficult to effectively regulate the platinum electronic structure.
Multi-component platinum-bismuth-based intermetallic ordered nanosheets are used as catalysts to form an intermetallic ordered structure and two-dimensional nanosheets composed of platinum, bismuth and auxiliary metal elements (such as iridium, ruthenium, osmium, rhodium, tin, lead). Topomorphology, improve catalytic performance.
The catalyst is achieved with high activity and high stability, and the electrocatalytic properties such as formic acid oxidation and methanol oxidation are significantly improved, especially in acidic conditions, which show excellent stability.
Smart Images

Figure CN119447342A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of multi-metal alloy catalysts, and in particular to a multi-component platinum-bismuth-based metal ordered nanosheet and a preparation method and application thereof. Background Art
[0002] Platinum-based multi-metal alloy catalysts are key catalytic materials for energy devices such as fuel cells. Changing the composition of catalytic materials and regulating the electronic structure of metal atoms are effective strategies to optimize the adsorption / desorption of reaction intermediates and improve catalytic performance. Alloying platinum (Pt) with other transition metals (M) (PtM, M = Fe / Co / Ni / Cu) can not only adjust the d-band center position of Pt and optimize the binding energy between Pt and reaction intermediates, but also effectively reduce the loading of metal platinum. However, due to thermodynamic limitations, the M atoms in traditional alloys (PtM) have limited control over the electronic structure of platinum; the diffusion barrier of M atoms is low and the durability is poor. How to improve the catalytic activity and stability of traditional alloy nanomaterials has always been one of the core issues in the field of fuel cell catalytic reactions. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a multi-component platinum-bismuth-based metal ordered nanosheet and its preparation method and application. The multi-component platinum-bismuth-based metal ordered nanosheet provided by the present invention is used as a catalyst in a fuel cell and has excellent electrocatalytic performance.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a multi-component platinum-bismuth-based ordered metal nanosheet, comprising a platinum element, a bismuth element and an auxiliary metal element, wherein the auxiliary element comprises 1 to 4 of iridium element, ruthenium element, osmium element, rhodium element, tin element and lead element, and the multi-component platinum-bismuth-based ordered metal nanosheet has an ordered metal structure and a two-dimensional nanosheet morphology.
[0006] Preferably, the molar percentage of each metal element in the multi-component platinum-bismuth-based intermetallic ordered nanosheets is independently 5 to 65%.
[0007] Preferably, the multi-component platinum-bismuth-based ordered metal nanosheets have a diameter of 20 to 25 nm and a thickness of 4 to 5 nm.
[0008] The present invention provides a method for preparing the multi-component platinum-bismuth-based metal ordered nanosheets described in the above technical solution, comprising the following steps:
[0009] A platinum source, a bismuth source, an auxiliary metal source, a reducing agent, a surfactant and an organic solvent are mixed to obtain a precursor dispersion; the auxiliary metal source comprises 1 to 4 of an iridium source, a ruthenium source, an osmium source, a rhodium source, a tin source and a lead source;
[0010] heating the precursor dispersion to obtain a black colloidal dispersion;
[0011] The black colloidal dispersion is mixed with a cyclohexane-ethanol mixed solution and centrifuged, and the obtained precipitate is washed to obtain the multi-component platinum-bismuth-based metal ordered nanosheets.
[0012] Preferably, the platinum source includes one or more of platinum acetylacetonate, chloroplatinic acid and potassium chloroplatinate; the bismuth source includes bismuth acetate and / or bismuth nitrate; the iridium source includes iridium acetylacetonate and / or iridium chloride; the ruthenium source includes one or more of ruthenium acetylacetonate, triruthenium dodecacarbonyl and ruthenium chloride; the osmium source includes triosmium dodecacarbonyl and / or osmium chloride; the rhodium source includes rhodium acetylacetonate and / or rhodium chloride; the tin source includes tin acetylacetonate and / or tin chloride; the lead source includes lead acetylacetonate and / or lead acetate.
[0013] Preferably, the reducing agent includes one or more of glucose, citric acid and ascorbic acid; the surfactant includes one or more of quaternary ammonium salt, halide salt and polyvinyl pyrrolidone; and the organic solvent includes one or more of oleylamine, octadecene, ethylene glycol and benzyl alcohol.
[0014] Preferably, the concentration of the platinum source in the precursor dispersion is 1-2 mg / mL, the concentration of the bismuth source is 0.5-2 mg / mL, the concentration of each auxiliary metal source is independently 0.5-2 mg / mL, the concentration of the reducing agent is 3-5 mg / mL, and the concentration of the surfactant is 3-5 mg / mL.
[0015] Preferably, the heating temperature is 180-230° C., and the insulation time is 30-300 min.
[0016] The present invention provides the use of the multi-component platinum-bismuth-based metal ordered nanosheets described in the above technical solution or the multi-component platinum-bismuth-based metal ordered nanosheets prepared by the preparation method described in the above technical solution as catalysts in fuel cells.
[0017] Preferably, the application comprises catalytic oxidation of formic acid or alcohols, the alcohols comprising methanol and / or ethanol.
[0018] The present invention provides a multi-component platinum-bismuth-based ordered metal nanosheet, comprising platinum, bismuth and auxiliary metal elements, wherein the auxiliary elements include 1 to 4 of iridium, ruthenium, osmium, rhodium, tin and lead, and the multi-component platinum-bismuth-based ordered metal nanosheet has an ordered metal structure and a two-dimensional nanosheet morphology. The multi-component platinum-bismuth-based ordered metal nanosheet provided by the present invention not only has the structural characteristics of high active sites of two-dimensional nanosheets, but also combines the unique electronic structure regulation advantages of the ordered metal structure, so that the series of catalysts exhibit excellent electrocatalytic performance, including formic acid oxidation electrocatalytic performance and methanol and ethanol oxidation electrocatalytic performance.
[0019] The present invention provides a method for preparing the multi-component platinum-bismuth-based metal ordered nanosheets described in the above technical solution. The present invention adopts a wet chemical organic phase preparation method, which has mild preparation conditions and simple operation, and effectively avoids problems such as catalyst agglomeration caused by high-temperature calcination to convert to an ordered phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a transmission electron microscope image of the hexameric high-entropy platinum-bismuth-based ordered intermetallic nanosheets prepared in Example 4;
[0021] Figure 2 This is a transmission electron microscope image of the hexameric high-entropy platinum-bismuth-based ordered intermetallic nanosheets prepared in Example 4;
[0022] Figure 3 The X-ray diffraction pattern of the hexameric high-entropy platinum-bismuth-based ordered intermetallic nanosheets prepared in Example 4;
[0023] Figure 4 This is a comparison chart of the formic acid oxidation activities of a series of multi-component platinum-bismuth-based metal ordered nanosheets prepared in Examples 1 to 4 and a commercial Pt / C catalyst under acidic conditions;
[0024] Figure 5 This is a comparison chart of the formic acid oxidation stability performance of the six-element high entropy platinum-bismuth-based metal ordered nanosheets prepared in Example 4 and the commercial Pt / C catalyst under acidic conditions;
[0025] Figure 6 This is a comparison chart of the methanol oxidation activity of a series of multi-component platinum-bismuth-based metal ordered nanosheets prepared in Examples 1 to 4 and a commercial Pt / C catalyst under acidic conditions;
[0026] Figure 7 This is a comparison chart of the methanol oxidation stability performance of the hexameric high-entropy platinum-bismuth-based metal ordered nanosheets prepared in Example 4 and the commercial Pt / C catalyst under acidic conditions. DETAILED DESCRIPTION
[0027] The present invention provides a multi-component platinum-bismuth-based ordered metal nanosheet, comprising a platinum element, a bismuth element and an auxiliary metal element, wherein the auxiliary element comprises 1 to 4 of iridium element, ruthenium element, osmium element, rhodium element, tin element and lead element, and the multi-component platinum-bismuth-based ordered metal nanosheet has an ordered metal structure and a two-dimensional nanosheet morphology.
[0028] In the present invention, when the auxiliary element includes one of iridium, ruthenium, osmium, rhodium, tin and lead, the multi-component platinum-bismuth-based ordered metal nanosheets are ternary low-entropy platinum-bismuth-based ordered metal nanosheets. In an embodiment of the present invention, the ternary low-entropy platinum-bismuth-based ordered metal nanosheets are platinum-bismuth-iridium ordered metal nanosheets. In the present invention, when the auxiliary element includes two of iridium, ruthenium, osmium, rhodium, tin and lead, the multi-component platinum-bismuth-based ordered metal nanosheets are quaternary medium-entropy platinum-bismuth-based ordered metal nanosheets. In an embodiment of the present invention, the quaternary medium-entropy platinum-bismuth-based ordered metal nanosheets are platinum-bismuth-iridium-rhodium ordered metal nanosheets. In the present invention, when the auxiliary element includes 3 of iridium, ruthenium, osmium, rhodium, tin and lead, the multi-component platinum-bismuth-based metal ordered nanosheets are five-element high-entropy platinum-bismuth-based metal ordered nanosheets. In the implementation of the present invention, the five-element high-entropy platinum-bismuth-based metal ordered nanosheets are platinum-bismuth-iridium-rhodium-osmium metal ordered nanosheets. In the present invention, when the auxiliary element includes 4 of iridium, ruthenium, osmium, rhodium, tin and lead, the multi-component platinum-bismuth-based metal ordered nanosheets are six-element high-entropy platinum-bismuth-based metal ordered nanosheets. In an embodiment of the present invention, the six-element high-entropy platinum-bismuth-based metal ordered nanosheets are platinum-bismuth-iridium-rhodium-osmium-ruthenium metal ordered nanosheets. In the present invention, the molar percentage of each metal element in the multi-component platinum-bismuth-based metal ordered nanosheets is preferably independently 5 to 65%, and more preferably independently 9 to 42%.
[0029] In the present invention, the multi-component platinum-bismuth-based ordered metal nanosheets have an ordered metal structure and a two-dimensional nanosheet morphology (the thickness of the nanosheet is in the nanometer size). The diameter of the multi-component platinum-bismuth-based ordered metal nanosheets is preferably 20 to 25 nm, and the thickness is preferably 4 to 5 nm.
[0030] The invention constructs a multi-metal intermetallic ordered nanosheet material, which has high activity and high stability.
[0031] The present invention provides a method for preparing the multi-component platinum-bismuth-based metal ordered nanosheets described in the above technical solution, comprising the following steps:
[0032] A platinum source, a bismuth source, an auxiliary metal source, a reducing agent, a surfactant and an organic solvent are mixed to obtain a precursor dispersion; the auxiliary metal source comprises 1 to 4 of an iridium source, a ruthenium source, an osmium source, a rhodium source, a tin source and a lead source;
[0033] heating the precursor dispersion to obtain a black colloidal dispersion;
[0034] The black colloidal dispersion is mixed with a cyclohexane-ethanol mixed solution and centrifuged, and the obtained precipitate is washed to obtain the multi-component platinum-bismuth-based metal ordered nanosheets.
[0035] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.
[0036] The invention mixes a platinum source, a bismuth source, an auxiliary metal source, a reducing agent, a surfactant and an organic solvent to obtain a precursor dispersion liquid; the auxiliary metal source comprises 1 to 4 of an iridium source, a ruthenium source, an osmium source, a rhodium source, a tin source and a lead source.
[0037] In the present invention, the platinum source preferably includes one or more of platinum acetylacetonate, chloroplatinic acid and potassium chloroplatinate; the bismuth source preferably includes bismuth acetate and / or bismuth nitrate; the iridium source preferably includes iridium acetylacetonate and / or iridium chloride; the ruthenium source preferably includes one or more of ruthenium acetylacetonate, triruthenium dodecacarbonyl and ruthenium chloride; the osmium source preferably includes triosmium dodecacarbonyl and / or osmium chloride; the rhodium source preferably includes rhodium acetylacetonate and / or rhodium chloride; the tin source preferably includes tin acetylacetonate and / or tin chloride; the lead source preferably includes lead acetylacetonate and / or lead acetate. In the present invention, the reducing agent preferably includes one or more of glucose, citric acid and ascorbic acid; the surfactant preferably includes one or more of quaternary ammonium salt, halide salt (i.e., salt containing halide ions) and polyvinylpyrrolidone (PVP), the quaternary ammonium salt is preferably hexadecyltrimethylammonium chloride, and the halide salt is preferably ammonium bromide; the organic solvent preferably includes one or more of oleylamine, octadecene, ethylene glycol and benzyl alcohol.
[0038] In the present invention, the mixing method is preferably ultrasonic stirring, the ultrasonic power of the ultrasonic stirring is preferably 50 to 100 W, and can be 60, 70, 80 or 90 W, and the time is preferably 30 to 90 min, and can be 50, 60 or 70 min. After the ultrasonic stirring, a uniformly dispersed precursor dispersion is obtained, and the precursor dispersion is turbid and uniformly colloid.
[0039] In the present invention, the concentration of the platinum source in the precursor dispersion is preferably 1-2 mg / mL, and can be 1 or 2 mg / mL. The concentration of the bismuth source is preferably 0.5-2 mg / mL, and can be 0.5, 1, 1.5 or 2 mg / mL. The concentration of each auxiliary metal source is preferably independently 0.5-2 mg / mL, and can be independently 0.5, 1, 1.5 or 2 mg / mL. The concentration of the reducing agent is preferably 3-5 mg / mL, and can be 3, 3.5, 4, 4.5 or 5 mg / mL. The concentration of the surfactant is preferably 3-5 mg / mL, and can be 3, 3.5, 4, 4.5 or 5 mg / mL.
[0040] After obtaining the precursor dispersion, the present invention heats the precursor dispersion to obtain a black colloidal dispersion. In the present invention, the heating temperature is preferably 180-230°C, more preferably 200-230°C, and further preferably 220-230°C, and the insulation time is preferably 30-300min, more preferably 60-180min, and further preferably 60-100min; the heating is preferably oil bath heating, that is, the precursor dispersion is transferred to an oil bath pot for heating. During the heating process, chemical nucleation growth is carried out to obtain a black colloidal dispersion containing a two-dimensional intermetallic ordered nanosheet product.
[0041] After obtaining the black colloidal dispersion, the present invention mixes the black colloidal dispersion with a cyclohexane-ethanol mixed solution and centrifuges it, washes the obtained precipitate, and obtains the multi-component platinum-bismuth-based metal ordered nanosheets.
[0042] In the present invention, the volume ratio of cyclohexane-ethanol in the cyclohexane-ethanol mixed solution is preferably 2:1, and the volume ratio of the black colloidal dispersion to the cyclohexane-ethanol mixed solution is preferably 1-3:1-3, more preferably 5:3. In the present invention, the function of the cyclohexane-ethanol mixed solution is to separate the precipitated product. In the present invention, the black colloidal dispersion is preferably cooled to room temperature before adding the cyclohexane-ethanol mixed solution. In the present invention, the rotation speed of the centrifugation is preferably 8000-9500r / min, more preferably 9000r / min, and the time is preferably 3-5min.
[0043] In the present invention, the washing solution used for the washing is preferably a cyclohexane-ethanol mixed solution, and the volume ratio of cyclohexane to ethanol in the cyclohexane-ethanol mixed solution is preferably 1-3:1-3, more preferably 1:3; the number of times of the washing is preferably 2-3 times.
[0044] In the embodiment of the present invention, after obtaining the multi-component platinum-bismuth-based ordered metal nanosheets, the multi-component platinum-bismuth-based ordered metal nanosheets are preferably dispersed in cyclohexane to prepare a standby solution.
[0045] Compared with the disordered solid solution structure, the ordered structure between metals can not only regulate the surface electronic structure through uniaxial strain, but also has strong structural stability in strong acid. Moreover, in order to enhance the application of catalytic materials in actual membrane electrodes, it is often necessary to design catalytic materials with ultra-high specific surface area to improve the surface transmission impedance, which also poses new challenges to the number of active sites on the surface of traditional alloy materials. Among various types of platinum-based nanomaterials, two-dimensional platinum-based multi-metal materials have attracted attention due to their large specific surface area and strong contact with the carrier, making them have great potential for application in various energy catalysis fields. However, due to the dual limitations of thermodynamics and kinetics, the construction of two-dimensional platinum-based materials is still a great challenge in the field of nanometal preparation. The present invention can more accurately regulate the reaction kinetics of the formation process of multi-component platinum-bismuth-based metal ordered nanosheets by controlling the concentrations of metal precursors, surfactants and reducing agents, reaction temperature and reaction time. The reaction conditions are mild, and the obtained multi-component platinum-bismuth-based metal ordered nanosheets have controllable microstructures, which are of great significance in the study of ordered metal alloys. The preparation method provided by the present invention is simple and feasible, and is easy to prepare on a large scale.
[0046] The present invention provides the use of the multi-component platinum-bismuth-based metal ordered nanosheets described in the above technical solution or the multi-component platinum-bismuth-based metal ordered nanosheets prepared by the preparation method described in the above technical solution as a catalyst in a fuel cell. In the present invention, the application preferably includes catalyzing the oxidation of formic acid or alcohol, and the alcohol preferably includes methanol and / or ethanol; the formic acid or alcohol oxidation is preferably carried out under acidic conditions. The present invention has no special requirements for the application method, and the application method familiar to those skilled in the art can be used.
[0047] In order to further illustrate the present invention, the multi-component platinum-bismuth-based intermetallic ordered nanosheets provided by the present invention and their preparation methods and applications are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0048] Example 1
[0049] The preparation steps of multi-component platinum-bismuth-based ordered metal nanosheets (ternary low-entropy platinum-bismuth-based ordered metal nanosheets) are as follows:
[0050] (1) Platinum acetylacetonate, bismuth acetate, iridium acetylacetonate, glucose and ammonium bromide were dissolved in oleylamine solvent at concentrations of 2 mg / mL, 1 mg / mL, 1.5 mg / mL, 3 mg / mL and 3 mg / mL, respectively, and ultrasonicated (ultrasonic power of 60 W) for 60 min to obtain a turbid and uniform colloidal precursor dispersion;
[0051] (2) transferring the precursor dispersion to an oil bath pot for oil bath heating, and keeping the dispersion warm after the dispersion is heated to 230° C., reacting the dispersion at this temperature for 60 minutes to generate a black colloidal dispersion, and then stopping heating;
[0052] (3) After the reaction container is cooled to room temperature, 3 mL of a cyclohexane-ethanol mixed solution (the volume ratio of cyclohexane to ethanol is 2:1) is added to 5 mL of the black colloidal dispersion, followed by centrifugation at 9000 r / min for 5 min, and then washed twice with a cyclohexane-ethanol mixed solution (the volume ratio of cyclohexane to ethanol is 1:3) to obtain a ternary low-entropy platinum bismuth iridium intermetallic ordered nanosheet with a diameter of 20 nm and a thickness of 4 nm, wherein the molar ratio of each metal element in the nanosheet is Pt:Bi:Ir=42:36:22.
[0053] Example 2
[0054] The preparation steps of multi-component platinum-bismuth-based ordered metal nanosheets (quaternary medium entropy platinum-bismuth-based ordered metal nanosheets) are as follows:
[0055] (1) Platinum acetylacetonate, bismuth acetate, iridium acetylacetonate, rhodium acetylacetonate, glucose and ammonium bromide were dissolved in oleylamine solvent at concentrations of 2 mg / mL, 1 mg / mL, 1.5 mg / mL, 1.5 mg / mL, 3 mg / mL and 3 mg / mL, respectively, and ultrasonicated (ultrasonic power of 70 W) for 70 min to obtain a turbid and uniform colloidal precursor dispersion;
[0056] (2) transferring the precursor dispersion to an oil bath pot for oil bath heating, and keeping the dispersion warm after the dispersion is heated to 230° C., reacting the dispersion at this temperature for 60 minutes to generate a black colloidal dispersion, and then stopping heating;
[0057] (3) After the reaction container is cooled to room temperature, 3 mL of a cyclohexane-ethanol mixed solution (the volume ratio of cyclohexane to ethanol is 2:1) is added to 5 mL of the black colloidal dispersion, followed by centrifugation at 9000 r / min for 5 min, and then washed twice with a cyclohexane-ethanol mixed solution (the volume ratio of cyclohexane to ethanol is 1:3) to obtain quaternary medium-entropy platinum bismuth iridium rhodium intermetallic ordered nanosheets with a diameter of 20 nm and a thickness of 4 nm, wherein the molar ratio of each metal element in the nanosheet is Pt:Bi:Ir:Rh=32:35:15:18.
[0058] Example 3
[0059] The preparation steps of multi-component platinum-bismuth-based ordered metal nanosheets (five-component high-entropy platinum-bismuth-based ordered metal nanosheets) are as follows:
[0060] (1) Platinum acetylacetonate, bismuth acetate, iridium acetylacetonate, rhodium acetylacetonate, triosmium dodecacarbonyl, glucose and ammonium bromide were dissolved in oleylamine solvent at concentrations of 2 mg / mL, 1 mg / mL, 1.5 mg / mL, 1.5 mg / mL, 1.5 mg / mL, 5 mg / mL and 5 mg / mL, respectively, and ultrasonicated (ultrasonic power of 80 W) for 70 min to obtain a turbid and uniform colloidal precursor dispersion;
[0061] (2) transferring the precursor dispersion to an oil bath pot for oil bath heating, and keeping the dispersion warm after the dispersion is heated to 230° C., reacting the dispersion at this temperature for 60 minutes to generate a black colloidal dispersion, and then stopping heating;
[0062] (3) After the reaction container is cooled to room temperature, 3 mL of cyclohexane-ethanol mixed solution (the volume ratio of cyclohexane to ethanol is 2:1) is added to 5 mL of the black colloidal dispersion, followed by centrifugation at 9000 r / min for 5 min, and then washed twice with cyclohexane-ethanol mixed solution (the volume ratio of cyclohexane to ethanol is 1:3) to obtain five-element high-entropy platinum bismuth iridium rhodium osmium intermetallic ordered nanosheets with a diameter of 20 nm and a thickness of 5 nm, wherein the molar ratio of each metal element in the nanosheet is Pt:Bi:Ir:Rh:Os=28:30:13:16:13.
[0063] Example 4
[0064] The preparation steps of multi-component platinum-bismuth-based ordered metal nanosheets (six-component high entropy platinum-bismuth-based ordered metal nanosheets) are as follows:
[0065] (1) Platinum acetylacetonate, bismuth acetate, iridium acetylacetonate, rhodium acetylacetonate, triosmium dodecacarbonyl, ruthenium acetylacetonate, glucose and ammonium bromide were dissolved in oleylamine solvent at concentrations of 2 mg / mL, 1 mg / mL, 1.5 mg / mL, 1.5 mg / mL, 1.5 mg / mL, 5 mg / mL and 5 mg / mL, respectively, and ultrasonicated (ultrasonic power of 90 W) for 70 min to obtain a turbid and uniform colloidal precursor dispersion;
[0066] (2) transferring the precursor dispersion to an oil bath pot for oil bath heating, and keeping the dispersion warm after the dispersion is heated to 230° C., reacting the dispersion at this temperature for 60 minutes to generate a black colloidal dispersion, and then stopping heating;
[0067] (3) After the reaction container is cooled to room temperature, 3 mL of a cyclohexane-ethanol mixed solution (the volume ratio of cyclohexane to ethanol is 2:1) is added to 5 mL of the black colloidal dispersion, followed by centrifugation at 9000 r / min for 5 min, and then washed twice with a cyclohexane-ethanol mixed solution (the volume ratio of cyclohexane to ethanol is 1:3) to obtain a hexameric high-entropy platinum bismuth iridium rhodium osmium ruthenium intermetallic ordered nanosheet with a diameter of 20 nm and a thickness of 5 nm, wherein the molar ratio of each metal element in the nanosheet is Pt:Bi:Ir:Rh:Os:Ru=20:31:14:15:11:9.
[0068] Figure 1 and Figure 2 These are transmission electron microscope images of six-element high entropy platinum-bismuth-based ordered metal nanosheets prepared in Example 4 at different scales. Figure 1 It can be seen that the diameter of the nanosheet is 20-25 nm; Figure 2 It can be seen that the thickness of the nanosheets is 4 to 5 nm.
[0069] Figure 3 This is the X-ray diffraction pattern of the hexameric high-entropy platinum-bismuth-based ordered metal nanosheets prepared in Example 4, showing an ordered structure.
[0070] The formic acid oxidation electrocatalytic performance of the multi-component platinum-bismuth-based ordered metal nanosheets prepared in the embodiment was tested. The test method and conditions were as follows: all electrochemical test data were collected by Shanghai Chenhua workstation, and the electrochemical formic acid oxidation performance test was carried out using a three-electrode system. The working electrode was a Pine disk electrode, the reference electrode was a saturated calomel electrode, and the counter electrode was a carbon rod; the formic acid oxidation electrolyte was a 0.1 M perchloric acid solution containing 0.5 M formic acid, the formic acid oxidation potential window was 0.1-1.1 V (vs. RHE), and the scan rate was 50 mVs -1 The stability test was conducted using IT technology at a voltage of 0.4 V for 5000 s. A commercial platinum-carbon (Pt / C) catalyst was used as a control. Figure 4 This is a comparison chart of the formic acid oxidation activity of a series of multi-component platinum-bismuth-based metal ordered nanosheets prepared in Examples 1 to 4 and a commercial Pt / C catalyst under acidic conditions. Figure 4 The ternary low entropy, quaternary medium entropy, quinary high entropy and hexavalent high entropy metal ordered nanosheet catalysts correspond to Example 1, Example 2, Example 3 and Example 4 respectively. Figure 4 It can be seen that the multi-component platinum-bismuth-based ordered metal nanosheet catalysts show excellent formic acid oxidation performance. Among them, the six-component high-entropy platinum-bismuth-based ordered metal nanosheets have the best performance. The reaction is a dehydrogenation pathway. At a voltage of 0.75 V, its formic acid oxidation mass activity is 12.4 Amg Pt -1 , which is about 62 times higher than commercial Pt / C. Figure 5This is a comparison of the formic acid oxidation stability performance of the six-element high entropy platinum-bismuth-based metal ordered nanosheets prepared in Example 4 and the commercial platinum-carbon catalyst under acidic conditions. Figure 5 It can be seen that the 5000s stability test results show that the mass activity of the hexavalent high-entropy metal ordered nanosheets is much higher than that of the commercial platinum-carbon catalyst.
[0071] The methanol oxidation electrocatalytic performance of the multi-component platinum-bismuth-based ordered metal nanosheets prepared in the example was tested. The test method and conditions were as follows: All electrochemical test data were collected by Shanghai Chenhua Workstation. The electrochemical methanol oxidation performance test was carried out using a three-electrode system. The working electrode was a Pine disk electrode, the reference electrode was a saturated calomel electrode, and the counter electrode was a carbon rod. The methanol oxidation electrolyte was a 0.1M perchloric acid solution containing 0.5M methanol. The methanol oxidation potential window was 0.1-1.1V (vs. RHE), and the scan rate was 50mVs -1 The stability test was conducted using IT technology at a voltage of 0.9 V for 5000 s. A commercial platinum-carbon (Pt / C) catalyst was used as a control. Figure 6 This is a comparison chart of the methanol oxidation activity of the series of multi-component platinum-bismuth-based metal ordered nanosheets prepared in Examples 1 to 4 and the commercial Pt / C catalyst under acidic conditions. Figure 6 It can be seen that the multi-component platinum-bismuth-based ordered metal nanosheet catalysts show excellent methanol oxidation performance. Among them, the six-component high-entropy platinum-bismuth-based ordered metal nanosheets have the best performance, with a methanol oxidation mass activity of 5.2Amg at a voltage of 0.9V. Pt -1 , which is about 5 times higher than commercial Pt / C. Figure 7 This is a comparison chart of the methanol oxidation stability performance of the six-element high entropy platinum-bismuth-based metal ordered nanosheets prepared in Example 4 and commercial platinum-carbon catalysts under acidic conditions. Figure 7 It can be seen that the 5000s stability test results show that the mass activity of the hexavalent high-entropy metal ordered nanosheets is much higher than that of the commercial platinum-carbon catalyst.
[0072] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A multi-component platinum-bismuth-based ordered metal nanosheet, characterized in that: It includes platinum, bismuth and auxiliary metal elements, wherein the auxiliary elements include 1 to 4 of iridium, ruthenium, osmium, rhodium, tin and lead. The multi-component platinum-bismuth-based intermetallic ordered nanosheets have an intermetallic ordered structure and a two-dimensional nanosheet morphology.
2. The multi-component platinum-bismuth-based ordered intermetallic nanosheet according to claim 1, characterized in that: The molar percentage of each metal element in the multi-component platinum-bismuth-based metal ordered nanosheet is independently 5-65%.
3. The multi-component platinum-bismuth-based ordered intermetallic nanosheet according to claim 1, characterized in that: The diameter of the multi-component platinum-bismuth-based metal ordered nanosheets is 20-25 nm, and the thickness is 4-5 nm.
4. The method for preparing the multi-component platinum-bismuth-based ordered intermetallic nanosheets according to any one of claims 1 to 3, characterized in that: The following steps are involved: A platinum source, a bismuth source, an auxiliary metal source, a reducing agent, a surfactant and an organic solvent are mixed to obtain a precursor dispersion; the auxiliary metal source comprises 1 to 4 of an iridium source, a ruthenium source, an osmium source, a rhodium source, a tin source and a lead source; heating the precursor dispersion to obtain a black colloidal dispersion; The black colloidal dispersion is mixed with a cyclohexane-ethanol mixed solution and centrifuged, and the obtained precipitate is washed to obtain the multi-component platinum-bismuth-based metal ordered nanosheets.
5. The preparation method according to claim 4, characterized in that: The platinum source includes one or more of platinum acetylacetonate, chloroplatinic acid and potassium chloroplatinate; the bismuth source includes bismuth acetate and / or bismuth nitrate; the iridium source includes iridium acetylacetonate and / or iridium chloride; the ruthenium source includes one or more of ruthenium acetylacetonate, triruthenium dodecacarbonyl and ruthenium chloride; the osmium source includes triosmium dodecacarbonyl and / or osmium chloride; the rhodium source includes rhodium acetylacetonate and / or rhodium chloride; the tin source includes tin acetylacetonate and / or tin chloride; the lead source includes lead acetylacetonate and / or lead acetate.
6. The preparation method according to claim 4, characterized in that: The reducing agent includes one or more of glucose, citric acid and ascorbic acid; the surfactant includes one or more of quaternary ammonium salt, halide salt and polyvinyl pyrrolidone; and the organic solvent includes one or more of oleylamine, octadecene, ethylene glycol and benzyl alcohol.
7. The preparation method according to claim 4, 5 or 6, characterized in that: The concentration of the platinum source in the precursor dispersion is 1-2 mg / mL, the concentration of the bismuth source is 0.5-2 mg / mL, the concentration of each auxiliary metal source is independently 0.5-2 mg / mL, the concentration of the reducing agent is 3-5 mg / mL, and the concentration of the surfactant is 3-5 mg / mL.
8. The preparation method according to claim 4, characterized in that: The heating temperature is 180-230° C., and the heat preservation time is 30-300 minutes.
9. Use of the multi-component platinum-bismuth-based ordered metal nanosheets according to any one of claims 1 to 3 or the multi-component platinum-bismuth-based ordered metal nanosheets prepared by the preparation method according to any one of claims 4 to 8 as catalysts in fuel cells.
10. The use according to claim 9, characterized in that: The applications include catalytic oxidation of formic acid or alcohols including methanol and / or ethanol.
Citation Information
Patent Citations
Platinum-based high-entropy alloy nanowire catalyst and preparation method thereof
CN114196981A
Preparation method of Pt-based high-entropy alloy with porous structure
CN115528257A
High-entropy alloy and preparation method thereof, membrane electrode assembly and fuel cell
CN116574957A
Palladium ruthenium-based high-entropy alloy nanosheet as well as preparation method and application thereof
CN117798357A
Preparation method and application of crystalline phase controllable PtBi2 intermetallic compound electrocatalyst
CN118835264A
Cited By
Platinum-germanium-based intermetallic ordered alloy catalyst as well as preparation method and application thereof
CN120715228A
A platinum-germanium based intermetallic ordered alloy catalyst, its preparation method and application
CN120715228B
Bent monatomic layer catalyst as well as preparation method and application thereof
CN122068052A